Co-existent Levels of Meaning in Mary’s Magnificat - Đurđica Garvanović-Porobija (Kairos (English Ed.), 2009)
Mary’s Magnificat is a lyric miniature with an emphatically rich semantic scope consisting of numerous levels identified by the author as: 1) the hymnal and poetic level, 2) the actors and action level, 3) the religious and ecclesiological level, 4) the revolutionary and subversive level, 5) the feminist and gender level, and 6) the maternal and familial level. A co-existence and openness in the polysemic structure of the Magnificat is outlined in this article which highlights messages for contemporary readers, especially for families. From Mary’s experience, which is spoken out in the Magnificat, as well as from the life of the holy family, one can separate special values: rapture through parenting, honor in the parent-child relationship, and awareness of the mission given to the child by God.